Pengelolaan Sampah dan Pengenalan Bank Sampah di Kecamatan Pondokgede - Anisa Pramitasari; Pretty Failasufa Aziza; Kiky Setyawati (P3M FIA UNKRIS, 2023)
Educating residents about waste management awareness and skills through the application of the principles of reduce, reuse, and recycle (3R) is crucial for solving waste problems through waste management from the source. A waste bank integrated with the 3R principles was implemented in Pondokgede District, Bekasi. The waste bank concept involves collecting and sorting dry waste and employing banking-like management, but instead of saving money, the savings are made from waste. The goal of this activity is to reduce the accumulation of household waste to prevent disasters and to utilize waste through creativity and innovation within the local community. The methods used are education, practice, and documentation. The results show that waste bank management provides numerous benefits to the surrounding community, creating a comfortable, beautiful, and green environment, and increasing community income. The conclusion of this study is that household waste can generate social, economic, and environmental benefits, resulting in a positive impact from the Waste Bank in Pondokgede District, Bekasi.